Marriage and Divorce in India : Changing Concepts and Practices - Bharati, Kanchan,; Lobo, Lancy, (Brill | Manohar Publishers & Distributors, 2019)
This volume explores the nature of social change in the fundamental institution of marriage in Indian society. It documents the churning going on in the conjugal bond with reference to gender inequality, patriarchy, domestic violence, divorce, separation, and remarriage under the impact of urbanization, modernization and globalization. The work includes fourteen papers divided into three parts. Part I discusses changes in the choice of spouse in terms of age at marriage and the age differential between spouses; endogamy and hypergamy; inter-caste and interfaith marriage; and divorce and remarriage among Hindus, Muslims and Christians with particular attention to feminism. It raises new questions about the rising trends of separation, desertion, divorce, remarriage, and the option to live single. Part II takes a closer look at love, sex and marital relationships through the prism of films, state laws, and civil rights. It specifically deals with the live-in relationships, extra-marital relations, matrimonial litigation, and use and abuse of IPC 498A. Part III documents the changing character of spouse selection through the newer forms such as the print and electronic media and the shift from parental choice to individual choice. The volume will interest students and scholars of sociology, social anthropology, family studies, and law, as well as counselors, various religious organizations, and electronic and print media.